Peroxidase from Coleus Forskohlii: Purification and Biochemical Characterization - Yaaser Q. Almulaiky (International Journal of Nutrition, 2020)
In this study, a peroxidase from new source was purified using ion exchange and gel filtration techniques. The recovery for peroxidase activity was 19% with 11-fold purification and specific activity of 749 unit/mg protein. Purified peroxidase demonstrated a molecular mass of 39 kDa using gel filtration and was confirmed as a single band on SDS-PAGE. The purified peroxidase revealed a broad optimum pH activity at 6.0-6.5 and 50°C temperature. The kinetic parameters for purified peroxidase toward H2O2 and guaiacol as substrates were found to be Km = 3.355, 5.395 mM, Kcat = 99.52, 79.56 s-1 and Vmax =1.531, 1.242 µmole ml-1 min-1, respectively. The catalytic efficiency (kcat/Km) of the purified peroxidase was 14.75 and 29.66 s−1 mM−1 for guaiacol and H2O2, respectively. Peroxidase activity was observed to be enhanced by Cu2+, Co2+, Ni2+ and inhibited in the presence of Sn2+, Al3+, Hg2+, NaN3, EDTA and urea. Characterization showed that peroxidase purified from C. forskohlii has the ability to be used for food industrial applications.
Keywords: Coleus forskohlii